Identification and analysis of lignin biosynthesis genes related to fruit ripening and stress response in banana (Musa acuminata L. AAA group, cv. Cavendish) - Wang, Zhuo; Yao, Xiao-ming; Jia, Cai-hong; Xu, Bi-yu; Wang, Jing-yi; Liu, Ju-hua; Jin, Zhi-qiang (Frontiers in Plant Science, 2023)
Lignin is the key component in the secondary cell wall of plants，which provides mechanical support and promotes water transport as well as has important impact responding to various biotic and abiotic stresses. In this study, we identified 104 genes from ten enzyme gene families related to lignin biosynthesis in Musa acuminata genome, and found the number of MaCOMT gene family was the largest, while MaC3Hs had only two members. MaPALs retained the original members, and the number of Ma4CLs in lignin biosynthesis was significantly less than that of flavonoids. Segmental duplication existed in most gene families, except MaC3Hs, and tandem duplication was the main way to expand the number of MaCOMTs. Moreover, the expression profiles of lignin biosynthesis genes during fruit development, posthavest ripening stages and under various abiotic and biotic stresses were investigated using available RNA-sequencing data to obtain fruit ripening and stress response candidate genes. Finally, a co-expression network of lignin biosynthesis genes was constructed by weighted gene co-expression network analysis to elucidate the lignin biosynthesis genes that might participate in lignin biosynthesis in banana during development and the response to stresses. This study systematically identified the lignin biosynthesis genes in the Musa acuminata genome, providing important candidate genes for further functional analysis. The identification of the major genes involved in lignin biosynthesis in banana provides the basis for the development of strategies to improve new banana varieties tolerant to biotic and abiotic stresses with high yield and high quality.